The Influence of the Problem-Based Learning Model Assisted by Short Video Learning on the Curiosity and Understanding of Science Subject Concepts of Grade III Elementary School Students - Novaritanti; Nurmalina; Kasman Ediputra (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This study aims to examine the influence of the Problem-Based Learning (PBL) model assisted by short video learning on the curiosity and concept understanding of third-grade students in science subjects at SD Negeri 15 Sungai Gayung Kiri. The research method used is a quasi-experimental design with a pretest-posttest control group. The population of this study is all third-grade students at SD Negeri 15 Sungai Gayung Kiri, with a research sample of 60 students divided into an experimental class and a control class. The experimental class was taught using the PBL model assisted by short video learning, while the control class received conventional teaching. The results showed significant differences in concept understanding and curiosity between the experimental and control classes after the implementation of the PBL model assisted by short video learning. The Mann-Whitney U test analysis for pretest and posttest indicated that the use of the PBL model assisted by short video learning significantly increased students' curiosity and concept understanding. This improvement can be attributed to the more interactive and engaging teaching methods that encouraged students to be more involved and interested in the material taught. The conclusion of this study is that the Problem-Based Learning (PBL) model assisted by short video learning is effective in enhancing students' curiosity and concept understanding in science subjects.